Interactions of ABCG2 (BCRP) with epidermal growth factor receptor kinase inhibitors developed for molecular imaging - Qawasmi, Israa; Shmuel, Miriam; Eyal, Sara (Frontiers in Pharmacology, 2014)
The objective of this study was to investigate in vitro the interactions between novel epidermal growth factor receptor kinase inhibitors (EGFRIs) developed for positron emission tomography (PET) imaging and the major efflux transporter breast cancer resistance protein (BCRP/ABCG2). Seven compounds were evaluated, using the ATPase activity assays and Madin-Darbey canine kidney (MDCK) cells overexpressing BCRP. Five of the tested compounds activated BCRP ATPase to various extent. Overexpression of BCRP conferred resistance to ML04, ML06, methoxy-Br-ML03 and PEG6-ML05 (IC50 values for inhibition of control cell proliferation 2.1 ± 0.6, 2.2 ± 0.7, 1.8 ± 1.2 and 2.8 ± 3.1 µM, respectively, compared to > 50 µM in MDCK-BCRP cells). At submicromolar concentrations, none of the EGFRIs significantly inhibited BCRP. Immunoblotting studies indicated that BCRP expression is evident in cell lines utilized for in vivo tumor grafting in small animal PET imaging studies. Thus, the intensity of EGFRIs radioactivity signals previously observed in tumor xenografts reflects an interplay between transporter-mediated distribution of the probe into tumor cells and target binding. Concomitant use of efflux transporter inhibitors may help distinguish between the contribution of efflux transport and EGFR binding to the tissue signal.